Basic Prototype of Islamic Boarding School Enterprise System : Purwarupa Dasar Sistem Enterprise Pondok Pesantren - Nova Andre Saputra; Darmanto Darmanto; Kevin Cornelius Septyanto (Universitas Muhammadiyah Sidoarjo, 2023)
The impact of Information Technology (IT) on the management of Islamic boarding schools (ponpes) is profound, yet administrative tasks often remain handled through traditional means, leading to inefficiencies. This research aims to address this gap by developing a basic prototype of an Islamic boarding school enterprise system, focusing on optimizing information management across various administrative domains. Employing the System Development Life Cycle (SDLC) prototype method, the study progresses through needs analysis, design, prototype construction, evaluation, implementation, and maintenance phases. The prototype system, tested at Darul Atsar Islamic boarding school, demonstrates significant improvements in academic, secretarial, student, financial management, and reporting processes. This study underscores the potential of IT integration to streamline routine tasks and enhance decision-making in Islamic educational institutions, contributing to broader discussions on educational technology adoption and management optimization. Highlights: Administrative efficiency: Enterprise system streamlines tasks across academic, secretarial, student, and financial domains. Data-driven decision-making: Prototype system empowers administrators with comprehensive reporting for strategic planning. Technological integration: IT solutions address traditional challenges, enhancing management practices. Keywords : Boarding School, Enterprise System, Prototype